Gyrokinetic study of ASDEX Upgrade inter-ELM pedestal profile evolution. (22nd May 2015) - Hatch, D.R.; Told, D.; Jenko, F.; Doerk, H.; Dunne, M.G.; Wolfrum, E.; Viezzer, E.; Pueschel, M.J.
Abstract: The gyrokinetic GENE code is used to study the inter-ELM H-mode pedestal profile evolution for an ASDEX Upgrade discharge. Density gradient driven trapped electron modes are the dominant pedestal instability during the early density-buildup phase. Nonlinear simulations produce particle transport levels consistent with experimental expectations. Later inter-ELM phases appear to be simultaneously constrained by electron temperature gradient (ETG) and kinetic ballooning mode (KBM) turbulence. The electron temperature gradient achieves a critical value early in the ELM cycle, concurrent with the appearance of both microtearing modes and ETG modes. Nonlinear ETG simulations demonstrate that the profiles lie at a nonlinear critical gradient. The nominal profiles are stable to KBM, but moderate increases in β are sufficient to surpass the KBM threshold. Certain aspects of the dynamics support the premise of KBM-constrained pedestal evolution; the density and temperature profiles separately undergo large changes, but in a manner that keeps the pressure profile constant and near the KBM limit.